Pemanfaatan brushing rubber dan silika dari sabut kelapa sebagai bahan pengisi dalam pembuatan kompon genteng karet - Nuyah . (Balai Riset dan Standardisasi Industri Palembang, 2014)
This study aims to determine the effect of brushing rubber and silica from coconut coir as a filler in the production of compound rubber tile, and get the rubber compound formula right and meet the requirements. The type of filler used is brushing rubber and silica filler material from the coconut coir with ratio variation were formula 1 (brushing rubber: silica = 22: 8), the formula 2 (brushing rubber: silica = 18: 12), the formula 3 (brushing rubber : silica = 15: 15), the formula 4 (brushing rubber: silica = 12: 18), the formula 5 (brushing rubber: silica = 8: 22) and the formula 6 (brushing rubber: silica = 4: 26). Results showed that the addition of rubber and silica brushing of coconut coir significantly affect the hardness, tensile strength, elongation at break and ozone resistance. The best formula obtained in the formula 3 (brushing rubber: silica = 15: 15) with a value of 50 shore A hardness, tensile strength of 6.3 MPa, elongation at break of 410% and Ozone resistance No cracks. Keywords : Brushing rubber, silica, rubber roof tiles compound AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan brushing rubber dan silika dari sabut kelapa sebagai bahan pengisi dalam pembuatan kompon genteng karet, serta mendapatkan formula kompon karet yang tepat dan memenuhi persyaratan. Jenis bahan pengisi yang digunakan yaitu brushing rubber dan bahan pengisi Silika dari sabut kelapa dengan variasi perbandingan yaitu formula 1 (brushing rubber : silika = 22 : 8), formula 2 (brushing rubber : silika = 18 : 12), formula 3 (brushing rubber : silika = 15 : 15), formula 4 (brushing rubber : silika = 12 : 18), formula 5 (brushing rubber : silika = 8 : 22)¸dan formula 6 (brushing rubber : silika = 4 : 26). Hasil Penelitian menunjukkan bahwa penambahan brushing rubber dan silika dari sabut kelapa berpengaruh nyata terhadap kekerasan, tegangan putus, perpanjangan putus dan Ozone resistance. Formula terbaik diperoleh pada formula 3(brushing rubber : silika = 15 : 15) dengan nilai kekerasan 50 shore A, tegangan putus 6,3 MPa, perpanjangan putus 410% dan Ozone resistance No cracks. Kata Kunci: Brushing rubber, Silika, kompon genteng karet.